1994
DOI: 10.1002/pssb.2221850214
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Piezoeffect in Semiconducting BiSb Alloys due to Anisotropy of Electron Mobility

Abstract: The strong electrical piezoeffect caused by the deformation induced anisotropy of electron mobility in Bi, _,Sb, semiconducting samples is described. Attention is drawn to the piezoeffect voltage, high in undoped samples, its nonsymmetric change under tensile and compressive deformation, and its sign inversion at small magnetic fields. All these effects are explained in terms of electron intervalley repopulation and scattering. Possible applications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The measurements of electrical piezoeffect in tellurium-doped semiconducting n-BiSb crystals at liquid nitrogen temperature show that under stretch in the direction of the binary C 2 axis the electron repopulation ratio is n 1 /n L > 0.9 at −ε xx ≈ 0.15%. Here n 1 is electron concentration in L 1 -valley and n L is electron concentration in all L 1 -, L 2 -, and L 3 -valleys [3]. This means that at liquid nitrogen temperature with ±ε xx ≈ 0.25% the repopulation of electrons into one or two valleys should be complete.…”
Section: Resistivity Of Uniaxially Deformed Polycrystallinementioning
confidence: 99%
See 2 more Smart Citations
“…The measurements of electrical piezoeffect in tellurium-doped semiconducting n-BiSb crystals at liquid nitrogen temperature show that under stretch in the direction of the binary C 2 axis the electron repopulation ratio is n 1 /n L > 0.9 at −ε xx ≈ 0.15%. Here n 1 is electron concentration in L 1 -valley and n L is electron concentration in all L 1 -, L 2 -, and L 3 -valleys [3]. This means that at liquid nitrogen temperature with ±ε xx ≈ 0.25% the repopulation of electrons into one or two valleys should be complete.…”
Section: Resistivity Of Uniaxially Deformed Polycrystallinementioning
confidence: 99%
“…[1] and in magnetoplasma waves at 77 K in Refs. [2,3]. It was shown that the anisotropy and orientation of the Fermi surface hole "ellipsoid" and electron "ellipsoids" remain unchanged in a wide range of deformations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrical piezoeffect measurements in tellurium-doped semiconducting n-Bi-Sb crystals at liquid nitrogen temperature show that under strain in the direction of the binary C 2 axis for +ε xx > 0.1% the electron repopulation rate n 1 /(3n) is > 0.8. Here n 1 is electron concentration in valley L 1 and 3n is electron concentration in valleys L 1 , L 2 , and L 3 [3].…”
Section: Longitudinal Resistivity Of Deformed Polycrystalline N-bi Filmsmentioning
confidence: 99%
“…The strain in direction of C 2 axis causes the transitions of electrons from valleys L 2 and L 3 to valley L 1 with high anisotropy of electron mobility. The electrical piezoeffect caused by the deformation-induced anisotropy of electron mobility in the semiconducting Bi 1−x Sb x was measured by the crossed induction coil technique [3].…”
Section: Introductionmentioning
confidence: 99%